2018
DOI: 10.1007/s10803-018-3559-0
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Memory for Self-Performed Actions in Adults with Autism Spectrum Disorder: Why Does Memory of Self Decline in ASD?

Abstract: The decline in self-related memory in ASD was investigated by using encoding, forgetting, and source monitoring. Participants memorized action sentences verbally, observationally, or by enacted encoding. Then, they underwent recall, recognition, and source monitoring memory tests immediately and 1 week later. If the information were properly encoded, memory performance in the enacted encoding would be the highest (enactment effect). The result of memory tests in ASD and TD people showed that enacted encoding w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Critically, autistic individuals can utilise the relations among items and produce narratives of a similar quality to TD individuals when the task is structured in a manner that enables the person to organise their responses (e.g., Bowler et al, 1997Bowler et al, , 2000Bowler et al, , 2008Hermelin & O'Connor, 1970;Losh & Gordon, 2014;Tager-Flusberg, 1991). For example, when test procedures involve cued and directed recall or recognition retrieval questioning techniques, autistic individuals' performance is often equivalent to that of TD comparison participants (e.g., Bennetto et al, 1996;Bowler et al, 1997Bowler et al, , 2004Bowler et al, , 2008Bowler, Gaigg, & Gardiner, 2015;Hare, Mellor, & Azmi, 2007;Zalla et al, 2010;Maras & Bowler, 2011;Maras et al, 2012Maras et al, , 2013Yamamoto & Masumoto, 2018). This pattern of memory performance in ASD suggests that difficulties arising during spontaneous memory retrieval can be compensated through appropriate scaffolds, which has led to the formulation of the Task Support Hypothesis (Bowler et al, 1997, positing that memory performance in ASD is enhanced on tasks that provide more support for the to-be-remembered material at test.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Critically, autistic individuals can utilise the relations among items and produce narratives of a similar quality to TD individuals when the task is structured in a manner that enables the person to organise their responses (e.g., Bowler et al, 1997Bowler et al, , 2000Bowler et al, , 2008Hermelin & O'Connor, 1970;Losh & Gordon, 2014;Tager-Flusberg, 1991). For example, when test procedures involve cued and directed recall or recognition retrieval questioning techniques, autistic individuals' performance is often equivalent to that of TD comparison participants (e.g., Bennetto et al, 1996;Bowler et al, 1997Bowler et al, , 2004Bowler et al, , 2008Bowler, Gaigg, & Gardiner, 2015;Hare, Mellor, & Azmi, 2007;Zalla et al, 2010;Maras & Bowler, 2011;Maras et al, 2012Maras et al, , 2013Yamamoto & Masumoto, 2018). This pattern of memory performance in ASD suggests that difficulties arising during spontaneous memory retrieval can be compensated through appropriate scaffolds, which has led to the formulation of the Task Support Hypothesis (Bowler et al, 1997, positing that memory performance in ASD is enhanced on tasks that provide more support for the to-be-remembered material at test.…”
mentioning
confidence: 99%
“…For example, when test procedures involve cued and directed recall or recognition retrieval questioning techniques, autistic individuals’ performance is often equivalent to that of TD comparison participants (e.g. Bennetto et al, 1996 ; Bowler et al, 1997 , 2004 , 2008 , 2015 ; Hare et al, 2007 ; Maras & Bowler, 2011 ; Maras et al, 2012 , 2013 ; Yamamoto & Masumoto, 2018 ; Zalla et al, 2010 ). This pattern of memory performance in ASD suggests that difficulties arising during spontaneous memory retrieval can be compensated through appropriate scaffolds, which has led to the formulation of the Task Support Hypothesis ( Bowler et al, 1997 , 2004 ), positing that memory performance in ASD is enhanced on tasks that provide more support for the to-be-remembered material at test.…”
mentioning
confidence: 99%
“…O’Shea and colleagues [ 28 ] found that recall accuracy was lower in ASD only for free recall, but not for cued recall. Yamamoto and Masumoto [ 29 ] also found decreased free recall accuracy in ASD.…”
Section: Resultsmentioning
confidence: 99%
“…SM accuracy was measured in 14 studies either as the number of sources correctly identified, in proportion to the total number of items presented, or as the proportion of correct responses among correctly identified old items (see Table A2 ). Overall, seven studies found reduced SM accuracy in ASD [ 3 , 13 , 22 , 26 , 28 , 29 ]. Bowler and colleagues [ 27 ] found that ASD participants had lower SM accuracy when recalling sources without memory support, but when source options were provided, their performance was comparable to controls.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the enactment effect has been also investigated with populations affected by ASD, leading to seemingly inconsistent results. While, some studies have reported reduced or absent enactment effect in individuals with ASD as a result of impaired or diminished action-monitoring systems (Farrant et al, 1999; Millward et al, 2000; Wojcik et al, 2011), other studies reported evidence of intact enactment effects both in adults and in children with ASD (Grainger et al, 2013; Wojcik et al, 2011; Yamamoto & Masumoto, 2018). Mixed results also emerged within studies testing SPT in autism by means of different memory domains (Zalla et al, 2010), reflecting the overall heterogeneity of memory profiles within the autism spectrum.…”
Section: Introductionmentioning
confidence: 99%